Research trends and prospects in global riverine carbon fluxes: A bibliometric analysis - Wei Fang; Mohd Remy Rozainy Mohd Arif Zainol; Xianbao Zha; Pingping Luo (Ecological Indicators)
Rivers are critical conduits of transporting and transforming carbon from land to coastal margins. Accurate estimates of the riverine carbon fluxes (RCFs) are crucial in assessing global carbon budget. Recently, a growing number of research has been conducted in this field. However, there still lacks a systematic analysis concerning the emerging, development, current status, and future trends of RCFs in existing studies. To identify the major characteristics and evolution of the research on RCFs, this study adopts a bibliometric method to analyze the publications retrieved from Web of Science during 1997–2023. The information related to journals, collaboration, keywords, and research evolution is statistically analyzed and scientifically visualized through R studio, VOSviewer, and CiteSpace. Findings indicate that a total of 1,592 documents from 368 different journals related to RCFs have been published by 7,035 researchers affiliated with 2,019 institutes from 95 countries. Research on RCFs has sharply increased since 2009, with an average annual publication number of 115. Around 45% of the total publications are attributed to the research categories of Environmental Science, and the most productive journal, country, institute, and author are Science of the Total Environment, the USA, Chinese Academy of Sciences, and Worral from Durham University, respectively. The analysis of keywords demonstrates that current study on RCFs mainly focus on monitoring the fluxes of multiple forms of carbon in the fluvial systems, modeling the fluxes of riverine carbon at larger scales, elaborating the complex biogeochemical processes of riverine carbon transport. Future research should further investigate the index quantification, scaling algorithms, and modeling framework of RCFs. This study contributes to holistically understanding the evolution and prevailing trends in the field of RCFs, and better constraining the carbon budgets at the regional or global scales.